On-Demand Coupling of Electrically Generated Excitons with Surface Plasmons via Voltage-Controlled Emission Zone Position - Zakharko, Yuriy; Held, Martin; Sadafi, Fabrizio-Zagros; Gannott, Florentina; Mandavi, Ali; Peschel, Ulf; Klupp Taylor, Robin; Zaumseil, Jana (ACS Photonics, 2016)
The ability to confine and manipulate light below the diffraction limit is a major goal of future multifunctional optoelectronic/plasmonic systems. Here, we demonstrate the design and realization of a tunable and localized electrical source of excitons coupled to surface plasmons based on a polymer light emitting field-effect transistor (LEFET). Gold nanorods that are integrated into the channel support localized surface plasmons and serve as nanoantennas for enhanced electroluminescence. By precise spatial control of the near-infrared emission zone in the LEFET via the applied voltages the near-field coupling between electrically generated excitons and the nanorods can be turned on or off as visualized by a change of electroluminescence intensity. Numerical calculations and spectroscopic measurements corroborate significant local electroluminescence enhancement due to the high local density of photonic states in the vicinity of the gold nanorods. Importantly, the integration of plasmonic nanostructures hardly influences the electrical performance of the LEFETs, thus, highlighting their mutual compatibility in novel active plasmonic devices.
Keywords: surface plasmon polariton; organic semiconductor; field-effect transistor; electroluminescence; Purcell effect; active plasmonics

Trion Electroluminescence from Semiconducting Carbon Nanotubes - Jakubka, Florian; Grimm, Stefan; Zakharko, Yuriy; Gannott, Florentina; Zaumseil, Jana (ACS nano, 2014)
Near-infrared emission from semiconducting single-walled carbon nanotubes (SWNTs) usually results from radiative relaxation of excitons. By binding an additional electron or hole through chemical or electrochemical doping, charged three-body excitons, so-called trions, are created that emit light at lower energies. The energy difference is large enough to observe weak trion photoluminescence from doped SWNTs even at room temperature. Here, we demonstrate strong trion electroluminescence from electrolyte-gated, light-emitting SWNT transistors with three different polymer-sorted carbon nanotube species, namely, (6,5), (7,5) and (10,5). The red-shifted trion emission is equal to or even stronger than the exciton emission, which is attributed to the high charge carrier density in the transistor channel. The possibility of trions as a radiative relaxation pathway for triplets and dark excitons that are formed in large numbers by electron-hole recombination is discussed. The ratio of trion to exciton emission can be tuned by the applied voltages, enabling voltage-controlled near-infrared light sources with narrow line widths that are solution-processable and operate at low voltages (<3 V).
EAM Import::2019-03-13